A common genetic variant in FOXP2 is associated with language‐based learning (dis)abilities: Evidence from two Italian independent samples. Issue 5 (24th April 2017) - Mozzi, Alessandra; Riva, Valentina; Forni, Diego; Sironi, Manuela; Marino, Cecilia; Molteni, Massimo; Riva, Stefania; Guerini, Franca R.; Clerici, Mario; Cagliani, Rachele; Mascheretti, Sara
Abstract : Language‐based Learning Disabilities (LLDs) encompass a group of complex, comorbid, and developmentally associated deficits in communication. Language impairment and developmental dyslexia (DD) represent the most recognized forms of LLDs. Substantial genetic correlations exist between language and reading (dis)abilities. Common variants in the FOXP2 gene were consistently associated with language‐ and reading‐related neuropsychological and neuroanatomical phenotypes. We tested the effect of a FOXP2 common variant, that is, rs6980093 (A/G), on quantitative measures of language and reading in two independent Italian samples: a population‐based cohort of 699 subjects (3–11 years old) and a sample of 572 children with DD (6–18 years old). rs6980093 modulates expressive language in the general population sample, with an effect on fluency scores. In the DD sample, the variant showed an association with the accuracy in the single word reading task. rs6980093 shows distinct genetic models of association in the two cohorts, with a dominant effect of the G allele in the general population sample and heterozygote advantage in the DD cohort. We provide preliminary evidence that rs6980093 associates with language and reading (dis)abilities in two independent Italian cohorts. rs6980093 is an intronic SNP, suggesting that it (or a linked variant) modulates phenotypic association via regulation of FOXP2 expression. Because FOXP2 brain expression is finely regulated, both temporally and spatially, it is possible that the two alleles at rs6980093 differentially modulate expression levels in a developmental stage‐ or brain area‐specific manner. This might help explaining the heterozygote advantage effect and the different genetic models in the two cohorts.